Radio frequency radiation measurement for base tower station safety compliances: a case study in Pulau Pinang Malaysia - M. Khuzairi; H. A. Rahim; M. Abdulmalek; M. Nazri M. Warip (Bulletin of Electrical Engineering and Informatics, 2019)
The residence of Pulau Pinang and Malaysia generally are worried with the possible health effects due to Base Tower Station (BTS) radiation. Particularly, the residents of Pulau Pinang are utilizing their mobile phones for multiple kind of tasks including communications, browsing the internet and other applications. With the recent advances in mobile communication technologies, the end user demanded a better coverage, great communication services, and faster speed for internet browsing. To fulfill the demand, service provider and communication companies are providing plenty of communication base tower leading to the beliefs of that the tower emitted radiation and cause harmful effect to human health and voiced out and complain to the municipal councils in Malaysia. In this paper, a measurement was conducted to study electromagnetic fields (EMF) radiation level in Pulau Pinang. The measurement is compared with the international standard provided by International Commission of Non-Ionizing Radiation Protection (ICNIRP). Far field measurement of different values of long term evolution (LTE) exposure was demonstrated in radiofrequency (RF) shielded environment. LTE850, LTE1800 and LTE2600 field exposure was compared in term of its’ electrical field and power density that adhere to the standard provided by ICNIRP.